Pengaruh Pijat Oksitosin Terhadap Kelancaran Asi Pada Ibu Postpartum Di Wilayah Kerja UPTD Taktakan Tahun 2024 - Siska Pujianti; Wiwin Widyastuti (Jurnal Ners, 2025)
Breast milk (ASI) is the best food for newborn babies and is the only healthy food that babies need in the first months of life. However, not all mothers can give exclusive breast milk to their babies. Exclusive breastfeeding is breast milk given to babies from birth for six months, without adding or replacing it with other food or drinks (except medicines, vitamins and minerals) (Indonesian Ministry of Health, 2018. Oxytocin massage is one solution to overcome insufficient breast milk. The benefits of oxytocin massage are providing comfort to the mother, reducing breast milk blockages, stimulating the release of the hormone oxytocin, maintaining breast milk production when the mother and baby are sick (Delima, 2019). To determine the effect of oxytocin massage on smooth breastfeeding in postpartum mothers.This research is quantitative using a pre-experimental design with an approach (One Group Pre-Post Test Design). The sample in this research was carried out using the accidental sampling method, namely the technique of determining the sample by chance. Based on the research results, there was a significant difference between respondents before being given Oxytocin Massage and after being given Oxytocin Massage in the breast milk smoothness score (P-Value 0.000). There is regarding the effect of oxytocin massage on the smooth flow of breast milk in postpartum mothers in the Taktakan UPTD work area in 2024